Pelaksanaan dalam Menghidupkan Kembali Isro’ Mi’roj di Desa Racek - hidayat, Muhammad wahyu; Hasan, Pahlawan; Faiz, Muhammad; Ainul Yakin, Moh Gusaai; Patoni, Alpan; Maulana, Agung; Gilang, Muhamad; Rohim, Muhammad (Kalam Nusantara Institute, 2024)
Based on the study of most interpretive scholars, the event of Isra' Mi'raj is a very special and majestic event because at the beginning of the verse Allah says starting with the word